REFLECTION ON CONSERVATION-RESTORATION PRACTICE TODAY. A EUROPEAN PERSPECTIVE - Belishki, Stefan; Corr, Susan (Protection of Cultural Heritage, 2019)
Contemporary conservation-restoration practice is affected by theoretical and ethical principles and by social factors. They are often discussed separately, but their effect on the processes of conservation-restoration is complex and intertwined. This paper offers an overview of the development of professional codes of ethics in conservation-restoration and as they relate to and inform professional competences. It looks at how ethics and competences are defined and link with professional education. It also discusses relationships with other professions in the preservation of cultural heritage and the need for clarification on the role and obligation of these respective professions. The legal and social issues they generate at a European level are touched upon.